Solid Wastes Composition and Generation in Selected Hotels at Aba and Umuahia, Abia State, Nigeria - M.U. Chikwendu; U.I. Uchendu; C. Kanu (Journal of Applied Sciences and Environmental Management, 2019)
A comparative study on solid wastes composition and generation in selected hotels in Umuahia and Aba metropolis of Abia state was conducted with a single factor experiment in randomized complete block design to determine the types and quantities of municipal solid waste generated at specific location in the two municipalities with three replications in both locations. The result shows Food/putrescible waste and glass/bottles are generated significantly higher than any other wastes types with mean values (73.44kg, 59.89kg 58.77kg, 54.61kg) and respectively in Aba and Umuahia city followed by plastic and polybags with significant low in inert and textile waste with mean value of (14.4kg, 22.03kg) and (13.12kg, 17.28kg) in Umuahia and Aba respectively. The study recommend that waste should be sorted out into their various components at source before disposal and emphasis should be laid on reuse for waste reduction, reuse and recycling of waste to mitigate the problem of waste in our cities.